DEVELOPMENT OF A DNA VACCINE WITH NUCLEOPROTEIN GENE OF THE SARS-COV-2 VIRUS - Dewi, Ni Putu Sutrisna; Mahardika, I Gusti Ngurah Kade; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p37, 2023)
DNA vaccines have become an interesting area of research in the fight against infectious diseases in animals and humans. DNA vaccines are vaccine formulations that use DNA fragments as antigens. The DNA in vaccines contains genetic information extracted from the disease agent, such as a virus or bacteria, that it is trying to target. This research aims to develop DNA vaccines in animals and humans. We developed plasmid DNA clones with the Covid-19 virus nucleoprotein gene that was transformed into E. coli stellar bacteria. The vaccine was injected in mice. The antibody was tested using an Enzyme-linked immunosorbent assay with purified recombinant NP protein. The results of the study showed that a clone of plasmid DNA with the nucleoprotein gene of the SARS-Cov-2 virus could be developed and proven. Administration of plasmid DNA clones with nucleoprotein genes in mice could induce the formation of specific antibodies against the nucleoprotein of the SARS-Cov-2 virus. The antibodies were increased from week 1 to weeks 4 and 5 then decreased in week 6 post-vaccination.